Cloning of a gene (zot) encoding a new toxin produced by Vibrio cholerae. - Baudry, B (1992)
Live oral candidate cholera vaccines have previously been constructed by deletion of Vibrio cholerae sequences encoding the enzymatically active A subunit of the cholera toxin. However, volunteer studies have shown that these non-cholera toxin-producing strains still provoke mild to moderate diarrhea in some individuals. We recently reported the identification of a second toxin produced by V. cholerae which may be responsible for this residual diarrhea (A. Fasano, B. Baudry, D. W. Pumplin, S. S. Wasserman, B. D. Tall, J. M. Ketley, and J. B. Kaper, Proc. Natl. Acad. Sci. USA 88:5242-5246, 1991). This new toxigenic factor increases the permeability of rabbit ileal mucosa by affecting the structure of the intercellular tight junctions (zonula occludens). We now report the identification and cloning of the gene encoding this new toxin. This gene, named zot (for zonula occludens toxin), consists of a 1.3-kb open reading frame which could potentially encode a 44.8-kDa polypeptide. The location of the zot gene encoding the new toxin is immediately upstream of the ctx operon encoding cholera toxin.